The Improvement of Students’ Understanding Through Interactive E-book on Contextual Environmental Education in the Biology Education Study Program at Pattimura University - Sianturi, Advend Sri Rizki; Pradana, Sendy Putra (12 Waiheru, 2025)
This study aims to improve students' understanding through contextual-based interactive e-books integrated with waste management practice guidelines, in order to increase students' understanding and involvement in local environmental issues. Environmental education plays an important role in shaping students' awareness of the importance of environmental conservation. However, the learning process in the Biology Education Study Program at Pattimura University still faces obstacles, especially the limitation of practical and contextual materials. This research is quantitative research conducted in May 2025 with second semester students as subjects. The E-book development procedure refers to the adapted Borg & Gall model. The E-book contains material on the potential of Maluku's natural resources, environmental issues, management strategies, and practical guidelines. The results of the trial showed that the E-book received a very positive response from students with an average acceptance rate of 86.22%. The increase in comprehension scores from the pre-test to the post-test was 22.7 points (from 62.4 to 85.1). The paired t-test results showed a value of t(29)=13.45t with p < 0.0001, proving that there was a significant difference between the scores before and after using the interactive e-book. The increase in engagement scores after using the E-book (pre: M = 58.01, SD ≈ ), (post: M = 67.84, SD ≈ ), difference M = 9.82, t(29) = 13.45, p < 0.0001, indicates a significant increase in engagement, particularly in the aspects of behaviour in using exercises/quizzes, making digital notes, using interactive features, frequency of multimedia access, and consistency in completing topics. Thus, this contextual-based interactive E-book has been proven effective in improving understanding, engagement, and the relevance of environmental learning for students.